Strategi Kerjasama Perguruan Tinggi Keagamaan Islam Negeri dalam Meningkatkan Akreditasi Prodi - Ayu, Sovia Mas (Universitas Islam Negeri Raden Intan Lampung, 2019)
Increasing the accreditation in higher education institutions is an urgency for immediate improvement. This study aims to analyze any collaboration in Islamic Education (PAI) Study Program, describe the form of Islamic Education (PAI) study program cooperation strategy, and identify the supporting and inhibiting factors of cooperation in the Islamic Education (PAI) UIN Raden Intan Lampung especially in increasing the study programs accreditation. This research uses a descriptive qualitative approach, with the type of field research. Data sources in this study are part of the collaboration between UIN Raden Intan Lampung, chairman and secretary of Islamic Education (PAI) Study Program, students and alumnies of Islamic Education (PAI) study programs, and the head of MAN I Bandar Lampung. Based on the results of the study it can be seen that the Islamic Education (PAI) UIN Raden Intan Lampung Study Program has carried out several academic and non-academic cooperation agendas, including: conducting educational practices (PPL) with schools and madrasas, and cooperation in the field of community service in the form of practical work lectures (KKN), PAI study program cooperation strategy by preparing and supporting factors for students both academically and non-academically to be able to compete in the world of work.